Manajemen Program Ekstrakurikuler dalam Meningkatkan Prestasi Non Akademik Peserta Didik - Arwan Adik Priyanto; Benny Kurniawan; Muhyidin Muhyidin (LPPM Institut Agama Islam Nahdlatul Ulama Kebumen, 2024)
This research aims to explore the role of extracurricular management in improving non-academic achievements of students at SMK Ma'arif 6 Ayah Kebumen, focusing on supporting and inhibiting factors. A qualitative approach was employed, involving in-depth interviews with extracurricular managers, teacher advisors, and active participants in extracurricular activities. The main problem formulation of this research is how extracurricular management operates at SMK Ma'arif 6 Ayah Kebumen and what factors act as supporters or inhibitors in its implementation. The results indicate that extracurricular management at SMK Ma'arif 6 Ayah Kebumen has various supporting factors, such as commitment from managers, active participation from students, school support, and resource availability. However, several inhibiting factors were also identified, including resource limitations, inadequate training for teacher advisors, and challenges in planning and coordinating activities. To enhance the effectiveness of extracurricular management, this study recommends improvements in resource management, increased training for teacher advisors, and enhanced coordination between extracurricular managers and the school administration. These efforts are expected to optimize the contribution of extracurricular activities in enhancing the non-academic achievements of students at SMK Ma'arif 6 Ayah Kebumen